PENGARUH PERPUTARAN PERSEDIAAN, DEBT TO EQUITY RATIO (DER) DAN LIKUIDITAS (CR) TERHADAP PROFITABILITAS (ROA) PADA PERUSAHAAN SUBSEKTOR FOOD AND BEVERAGES DI BEI PERIODE 2014-2018 - Desi Ratnasari Surbakti; Dianty Putri Purba; Sulastri Simanungkalit (Lembaga Penelitian dan Pengabdian Masyarakat Universitass Darma Agung, 2019)
This research aimed at simultaneously and partially testing and analyzing the effect of Inventory Turn Over, Debt to Equity Ratio and Current Ratio on Return On Assets at Food and Beverages companies which were listed in Indonesia Stock Exchange in 2014-2018 period. The theories applied in this research were Inventory Turn Over, Debt to Equity Ratio, Current Ratio and Return On Assets theories and the relation of Inventory Turn Over, Debt to Equity Ratio, and Current Ratio with Return On Assets. The approach applies in this research was quantitative approach with descriptive method. This research done was an explanatory research. This research used the population of twenty one (21) Food and Beverages companies which were listed in Indonesia Stock Exchange in 2014-2018 period. The sample which consisted of five (5) companies in five years was taken by using purposive sampling technique. Adjusted R Square value was as much as 0.121 or 12.1 percent. This meant the variation or the measure of data dispersion from ROA (Y) was shown by the Inventory Turn Over of (X1), DER (X2) and CR (X3) meanwhile 87.9 percent was shown by other variables which were not analyzed in this research. From the result of the research, it was concluded that the variable of Debt to Equity Ratio partially had negative and significant effect on Return On Assets and Inventory Turn Over, Debt to Equity Ratio and Current Ratio simultaneously had significant effect on Return On Assets in the Food and Beverages companies which were listed in Indonesia Stock Exchange in 2014-2018 period.